Expression of Bone Morphogenetic Protein-7 Significantly Correlates With Non-small Cell Lung Cancer Progression and Prognosis: A Retrospective Cohort Study. (May 2019) - Aoki, Masaya; Umehara, Tadashi; Kamimura, Go; Imamura, Nobuhiro; Morizono, Shoichiro; Nonaka, Yuto; Tokunaga, Takuya; Takeda, Aya Harada; Maeda, Koki; Watanabe, Yui; Nagata, Toshiyuki; Otsuka, Tsunayuki; et al.
Background: Bone morphogenetic protein-7 (BMP-7) is a signaling molecule belonging to the transforming growth factor-β superfamily. Recent studies have demonstrated that BMP-7 is expressed in various human cancers and plays an important role in the progression of their cancers. The purpose of this study was to investigate the clinicopathologic and prognostic impact of BMP-7 expression in clinical samples of non-small cell lung cancer. Methods: This study enrolled 160 patients with non-small cell lung cancer who underwent complete resection. Expression of BMP-7 in cancer tissue was evaluated by immunohistochemistry. Correlations between expression of BMP-7 and clinicopathologic factors and prognosis were analyzed. Results: In non-small cell lung cancer, BMP-7 expression was identified not only in cell membranes but also in the cytoplasm of cancer cells. Expression of BMP-7 correlated with p-T ( P  = .047), N factor ( P  = .013), and p-stage ( P  = .046). Overall survival rate was significantly lower in the BMP-7-positive group than in the BMP-7-negative group ( P  = .004). Multivariate analysis indicated that BMP-7 expression was one of the independent prognosis factors of overall survival ( P  = .021). Furthermore, among patients with postoperative recurrence (n = 58), the BMP-7-positive group (n = 29) had a significantly poorer prognosis than the BMP-7-negative group (n = 29) ( P  = .012). Conclusions: Expression of BMP-7 in non-small cell lung cancer was correlated with clinicopathologic factors and poorer prognosis. BMP-7 expression may be a useful predictor of aggressive activity of tumor behavior and postoperative outcome of patients with non-small cell lung cancer.